KPI System (Global Journal of Management and Business Research, 2023)
Chapter One I Introduction a Background of the Study B ikroy com is a private company established in 2012 and has different sections which are especially dedicated to private and business advertisements for property electronics vehicles home appliances sports and jobs I choose this company because I found out about the company s KPI background and other facilities are very appealing and enchanting If I work with this company others will get the chance to know about it